The influence of height on a 10 week flexibility program applied in physical education classes - Martins, Ricardo (2017)
Physical Education plays a role helping students acquire long-lasting habits of physical activity and sports that will improve their overall health. Improving flexibility, namely through hamstring stretching, will help execute and sustain the motor activities in the daily life of students. The aim of the present study was to understand the influence of height in a flexibility program in physical education classes. The subjects of this investigation were 61 (35 males and 26 females) divided in two separated groups (control and experimental) in the ages of 10-18 years old (M= 12.96 ± 2.83) and height between 125-178cm (M= 152.84 ± 6.36) all of participants were students of elementary and high school from two different schools in Portugal. The intervention was conducted in ten consecutive weeks, being planned within three assessments (initial, intermediate and final) and all of the subjects were evaluated in hamstring flexibility through Active Knee Extension. The results of this study strongly suggest that the height has no influence on the flexibility of the students.